Pachymeningitis cranialis hypertrophica. Issue 9 (September 1985) - Moore, A P; Rolfe, E B; Jones, E L
Abstract : A case of pachymeningitis cranialis hypertrophica is described and the CT appearances are presented. The likely cause was syphilis, though sarcoidosis and tuberculosis were not completely excluded.